2002
DOI: 10.4049/jimmunol.168.8.3839
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Killer Ig-Like Receptor Repertoire on CD4+CD28null T Cells

Abstract: Killer Ig-like receptors (KIRs) are expressed on CD4+CD28null T cells, a highly oligoclonal subset of T cells that is expanded in patients with rheumatoid arthritis. It is unclear at what stage of development these T cells acquire KIR expression. To determine whether KIR expression is a consequence of clonal expansion and replicative senescence, multiple CD4+CD28null T cell clones expressing the in vivo dominant TCR β-chain sequences were identified in three patients and analyzed for their KIR gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 37 publications
7
78
0
Order By: Relevance
“…These clones shared identical TCR␣ and TCR␤ sequences, but one clone expressed KIR2DL3, but not other KIR, while the other clone did not express any KIR (data not shown). This confirmed that KIR expression can be acquired after TCR rearrangement (37). KIR2DL3, expressed at high levels on the CD4 ϩ KIR ϩ clone (Fig.…”
Section: Expression Of Functional Inhibitory Kir On Cmv-specific Cd4 supporting
confidence: 75%
“…These clones shared identical TCR␣ and TCR␤ sequences, but one clone expressed KIR2DL3, but not other KIR, while the other clone did not express any KIR (data not shown). This confirmed that KIR expression can be acquired after TCR rearrangement (37). KIR2DL3, expressed at high levels on the CD4 ϩ KIR ϩ clone (Fig.…”
Section: Expression Of Functional Inhibitory Kir On Cmv-specific Cd4 supporting
confidence: 75%
“…However, the Ag specificities of those populations have not been identified, and autoreactivity is only presumed due to the autologous MLR proliferation. Even though there is no direct evidence implicating these cells in RA, recent studies suggesting the expression of NK markers on CD4 ϩ CD28 Ϫ cells in patients with arthritis lend support to an important role of these cells in pathogenesis (9,34). If these cells were required for autoreactivity leading to the development of arthritis, we would have observed a much more severe disease in CD28-deficient animals.…”
Section: Discussionmentioning
confidence: 81%
“…The promiscuous activity of the KIR3DL1 promoter suggests that the trans-acting factors required for its activity are widely distributed. Given that KIR3DL1 is only expressed in cell populations that also express KIR2DL4 (16,23,30,31), these data implicate mechanisms other than proximal promoter regulation in restricting the expression of the KIR3DL1 gene.…”
Section: Tissue Specificity Of Promoter Activitymentioning
confidence: 82%
“…KIR3DL3 (otherwise known as KIR3DL7 or KIRC1) does not appear to be expressed by the circulating NK cell pool in many donors (29). Most reports indicate that all NK clones and KIR-positive T cell clones express KIR2DL4 transcripts (16,23,24,30,31). The upstream regions of both these KIR genes diverge significantly from those of KIR with variegated expression (26).…”
mentioning
confidence: 99%